The Kruskal Wallis Analysis of Indonesian Sharia Banking Post-Merger: Kruskal Wallis Analysis of Indonesian Sharia Banking Post-Merger - Hijriah, Amanah; Sari Rusmitasari (LPPM POLITEKNIK LP3I BANDUNG, 2024)
In 2020, the Ministry of BUMN decided to merge three Sharia banks in Indonesia, namely Bank Syariah Mandiri (BSM), BNI Syariah and BRI Syariah with the aim of contributing to the economy, increasing market share, as well as the aim of efficiency and increasing income from financing products. Since this phenomenon occurred, a lot of research has been carried out, one of which is examining the performance of Bank Syariah Indonesia after the merger process was carried out. This research aims to examine differences in the performance of Indonesian Sharia Banks in terms of efficiency and income aspects using the Kruskal Wallis method. It is hoped that this research can become a reference, knowledge and provide an overview for academics, the general public, customers and potential investors to assess whether the BUMN Ministry's decision to merge these three banks is considered effective and has had a positive impact on stakeholders and the banks themselves. The results of this study show that efficiency measured by EFF shows a difference, while P/L does not. Revenue as measured by ROA showed no difference, while NPM experienced changes after the merger.